Influence of the posterior cruciate ligament on kinematics of the knee during experimentally simulated clinical tests and activities of daily living. (22nd January 2021) - Moslemian, Alireza; Sidhu, Roger; Roessler, Philip; Wood, Ryan; Degen, Ryan; Getgood, Alan; Willing, Ryan
Abstract: Clinical outcomes following posterior cruciate ligament (PCL) reconstruction are often suboptimal. A better understanding of the biomechanical contributions of the PCL to knee stability under physiologic, clinically-relevant loading conditions could improve reconstruction techniques and outcomes. We employed a servohydraulic joint motion simulator to investigate the kinematics of intact and PCL-deficient knees during simulated clinical tests and activities of daily living (ADL), including gait, stair ascent and descent. PCL transection caused the tibia to be displaced posterior, relative to the intact joint, throughout flexion. PCL transection also increased the amount of posterior tibial displacement measured during posterior laxity testing by up to 9.6 ± 1.7 mm at 75° (p = 0.001). During internal-external rotational laxity testing, PCL transection increased the allowable internal and external rotation of the tibia, by up to 2.9 ± 0.5°at 90° (p = 0.001) and 1.0 ± 0.2° at 45° (p = 0.001), respectively. PCL transection did not have a significant effect on abduction–adduction kinematics or laxity, regardless of flexion angle. PCL transection resulted in a relative posterior displacement of the tibia during the stance phase of gait when the knee was extended (2.2 ± 2.2 mm, p = 0.045), and when the knee was flexed during stair ascent (2.4 ± 2.2 mm, p = 0.035) and descent (1.6 ± 1.4 mm, p = 0.037). Our results support previous studies of the role of the PCL on neutral joint kinematics and laxity, and provide new data quantifying the effect of PCL transection on AP kinematics during simulated ADL.